Floral resource distribution and fitness consequences for two solitary bee species in agricultural landscapes - Eckerter, Philipp W.; Albrecht, Matthias; Herzog, Felix; Entling, Martin H. (Basic and applied ecology, 2022)
•Reproduction of two Osmia species increased with landscape-wide pollen availability.•Woody semi-natural habitats contributed disproportionately to the Osmia diet.•Benefits of forest proximity to Osmia indicated functions beyond pollen supply.•Resource and land cover maps help to understand the spatial ecology of wild bees. Floral resources are crucial for wild pollinators. Identifying the spatio-temporal floral resource use of wild pollinators and effects of resource distribution on their development might help to promote them and their pollination services to crops in agricultural landscapes. We established populations of Osmia cornuta and Osmia bicornis, two solitary wild bees, in 24 agricultural landscapes with varying floral resource availability. Based on their pollen use, we mapped the landscape-scale distribution of the visited plants, estimated pooled specific floral resource availabilities and measured its effects on reproductive output. Woody semi-natural habitats such as hedgerows provided the majority of pollen sources for both Osmia species. Pollen use differed strongly between the two species. The offspring of both Osmia increased with availability of pooled specific pollen resources. In accordance with their preferred pollen types, offspring of O. cornuta increased with increasing cover of trees and shrubs of the Rosaceae family, and that of O. bicornis with increasing cover of Papaver rhoeas, Ranunculus acris and Quercus spp. as well as with the proximity to oilseed rape. In spite of their specific responses to pollen resources, the offspring of both species decreased with the distance to forest. The floral resource availability did not significantly affect the proportion of adult females and the weight of the offspring. As forest does not appear to be a main foraging habitat for both species, the benefit of forest proximity indicates an additional role of forest in addition to food availability. Specific flowering plants and forests should thus be conserved and enhanced to maintain and support O. cornuta, O. bicornis and likely other wild bee populations in agricultural landscapes. The combined information of land cover and detailed floral resource availability gives a deeper understanding into population processes in agricultural landscapes.